Preparation method of oil shale-based aggregate ultra-high performance concrete material

By sintering oil shale slag, glass powder and magnesium oxide, it forms oil shale-based fine aggregate, and combines it with modified phosphogypsum powder and composite cementitious materials, the strength caused by oil shale slag in ultra-high performance concrete is solved. The problems of insufficient and low permeability have achieved efficient utilization of cement resources and improvement of concrete structure strength.

CN119285320AActive Publication Date: 2025-01-10SHANDONG JUNHONG ENVIRONMENTAL PROTECTION TECH CO LTD

Patent Information

Application Number
CN202411430931.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-10
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

Oil shale slag in ultra-high performance concrete, as fine aggregate, leads to insufficient strength and low permeability, and low hydration of cement components leads to waste.

Method used

Oil shale slag, glass powder and magnesium oxide are sintered and broken to form fine oil shale-based aggregate, and combined with modified phosphogypsum powder and composite cementitious materials to improve the strength and resistance of concrete through hydration reaction. seepage, reduce the proportion of cement to reduce waste.

Benefits of technology

It significantly improves the strength and permeability of concrete, reduces the waste of cement components, and realizes the resource utilization of oil shale slag and the mechanical strength of concrete structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285320A_ABST
    Figure CN119285320A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an oil shale-based aggregate ultra-high performance concrete material, which comprises the following steps: (1) uniformly mixing oil shale slag, glass powder, lithium slag powder and magnesium oxide, sintering, cooling to room temperature after sintering, and crushing the sintered product to obtain an oil shale-based fine aggregate; (2) taking the following raw materials: a composite cementing material, the oil shale-based fine aggregate, fly ash, silica fume, modified ardealite powder, fibers, a water reducing agent, sodium hydroxide and / or potassium hydroxide; the composite cementing material is composed of Portland cement and mineral powder. The concrete material is obtained by uniformly mixing the raw materials, adding mixing water and uniformly stirring. According to the method disclosed by the invention, the problem that the strength and the impermeability of the ultra-high performance concrete material prepared by taking the oil shale residues as the fine aggregate are reduced is solved, and the problem that cement components of the ultra-high performance concrete material are wasted is relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ultra-high performance concrete preparation, and in particular to a method for preparing an oil shale-based aggregate ultra-high performance concrete material. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Ultra-High Performance Concrete (UHPC) has ultra-high strength, high toughness, and ultra-high durability. Its performance far exceeds that of traditional concrete materials. This is because UHPC does not include coarse aggregates, but instead forms a denser structure with lower porosity through the cooperation of millimeter-level aggregates, micron-level particles (cement, fly ash, mineral powder, etc.), submicron-level particles (silica fume, etc.) and reinforcing fibers. Therefore, UHPC also has excellent characteristics of preventing water penetration, which helps to reduce the volatilization of water inside the concrete and reduce cracking.

[0004] Compared with traditional concrete materials, the proportion of cement components in UHPC is higher. In addition, in order to minimize the pores left after the volatilization of mixing water, UHPC generally adopts a low water-cement ratio, which leads to a low degree of hydration of the cement components in UHPC. Studies show that it is only about 30%. Most of the cement particles are only used as fillers and are not hydrated to form cementing components. This leads to the failure of most cement components to play their due role, resulting in a waste of cement, because the main function of the cement component in concrete materials is to undergo hydration reactions to form cementing components to bind aggregates together, which is the main source of concrete structural strength. In addition, the fine aggregate in UHPC generally uses natural sand and gravel resources, and its mining has brought many environmental problems. Oil shale slag is a solid waste residue produced during shale oil mining. When oil shale slag is used to directly replace natural sand and gravel fine aggregate to prepare UHPC, due to the loose and porous characteristics of oil shale slag, it not only has insufficient strength, but also has a high water absorption rate, which will further aggravate the problem of low degree of hydration of cement components in UHPC, thereby causing the strength of UHPC to decrease and the impermeability to be insufficient. Summary of the invention

[0005] In view of the above problems, the present invention provides a method for preparing an oil shale-based aggregate ultra-high performance concrete material, which not only overcomes the problem of reduced strength and impermeability of UHPC prepared with oil shale slag as fine aggregate, but also alleviates the problem of waste of cement components in UHPC. To achieve the above objectives, the technical solution of the present invention is as follows.

[0006] A method for preparing an oil shale-based aggregate ultra-high performance concrete material comprises the following steps:

[0007] (1) The oil shale slag, glass powder, lithium slag powder and magnesium oxide are uniformly mixed and then sintered. After the mixture is sintered, the mixture is cooled to room temperature and the sintered product is crushed to obtain oil shale-based fine aggregate.

[0008] (2) Phosphogypsum powder, sodium stearate powder and liquid silane coupling agent are mixed and stirred evenly, and then the obtained mixed powder is ground to obtain modified phosphogypsum powder.

[0009] (3) Take the following raw materials: 110-130 parts by weight of composite cementitious material, 230-280 parts by weight of oil shale-based fine aggregate, 70-85 parts by weight of fly ash, 140-170 parts by weight of silica fume, 50-62 parts by weight of modified phosphogypsum powder, 20-25 parts by weight of fiber, 1.6-2.8 parts by weight of water reducer, and 1-2 parts by weight of sodium hydroxide and / or potassium hydroxide; the composite cementitious material is composed of silicate cement and mineral powder, wherein the silicate cement accounts for 30-40wt.%. After the above raw materials are mixed, mixing water is added at a water-cement ratio of 0.17-0.25 and stirred evenly to obtain a concrete material.

[0010] Furthermore, in step (1), the ratio of the oil shale slag, glass powder, lithium slag powder and magnesium oxide is 50-70 parts by weight: 30-42 parts by weight: 6-8.5 parts by weight: 15-23 parts by weight.

[0011] Furthermore, in step (1), the fineness of the oil shale slag is 20-50 mesh. Optionally, the fineness of the glass powder, lithium slag powder, and magnesium oxide is not less than 200 mesh.

[0012] Furthermore, in step (1), the sintering temperature is higher than the softening temperature of the glass powder, and the sintering time is 20 to 35 minutes. Optionally, in step (1), the softening temperature of the glass powder does not exceed 600° C. Preferably, the glass powder is made of waste glass.

[0013] Furthermore, in step (1), the particle size of the oil shale-based fine aggregate is 0.5-3 mm. Preferably, the mass ratio of particles with particle sizes of 0.5-1 mm, 1-2 mm, and 2-3 mm in the oil shale-based fine aggregate is 1.5-2:1:1.

[0014] Furthermore, in step (2), the sodium stearate is 25-33% of the mass of the phosphogypsum powder, and the liquid silane coupling agent is 2-2.5% of the mass of the phosphogypsum powder. Optionally, the liquid silane coupling agent includes at least one of KH550, KH560, KH570, etc. The sodium stearate powder and the silane coupling agent not only reduce the water absorption of the modified phosphogypsum powder, but also increase the lubricity of the phosphogypsum particles, which can delay the dissolution of residual phosphoric acid in the phosphogypsum on the one hand. On the other hand, the high water absorption of the phosphogypsum particles is avoided to affect the fluidity of the concrete. The silane coupling agent helps to connect the sodium stearate particles with the phosphogypsum particles to construct a sustained-release system.

[0015] Furthermore, in step (2), the fineness of the modified phosphogypsum powder is 300-400 mesh.

[0016] Further, in step (3), the fiber includes at least one of steel fiber, organic fiber, basalt fiber, etc. Optionally, the organic fiber includes at least one of polyethylene fiber, polyvinyl alcohol fiber, polypropylene fiber, polyacrylonitrile fiber, etc.

[0017] Furthermore, in step (3), the length of the fiber is 12 to 30 mm, and the diameter is 0.1 to 0.3 mm.

[0018] Furthermore, in step (3), the fineness of the composite cementitious material is 300-400 mesh.

[0019] Furthermore, in step (3), the water reducer includes at least one of a polycarboxylic acid water reducer, a naphthalene-based water reducer, a melamine-based water reducer, a lignin sulfonate water reducer, and a melamine water reducer.

[0020] Compared with the prior art, the present invention has at least the following beneficial technical effects:

[0021] On the one hand, due to the high porosity and insufficient strength of oil shale slag, it is easy to reduce the degree of hydration of cement components when using it as fine aggregate to prepare ultra-high performance concrete, resulting in a decrease in the strength and impermeability of concrete. The present invention is based on oil shale slag, and glass powder, lithium slag powder and magnesium oxide are added thereto and then sintered. The oil shale-based fine aggregate formed after crushing not only significantly reduces the porosity, but also can undergo hydration reaction to increase the content of cementitious components, thereby improving the strength and impermeability of concrete. This is because the glass powder is melted during the sintering process to fill the pores in the oil shale slag particles and coat the oil shale slag particles, which not only reduces the porosity but also improves the strength. At the same time, the lithium element in the lithium slag powder helps to reduce the softening temperature of the glass powder during the sintering process, reducing energy consumption while realizing the resource utilization of lithium slag.

[0022] On the other hand, in view of the problem that although the amount of cement used in traditional ultra-high performance concrete is large, the actual hydration rate is low, resulting in waste of cement components, the present invention uses mineral powder to replace most of the cement to form a composite cementitious material, which reduces the proportion of cement and reduces unnecessary waste. When the above-mentioned composite cementitious material and raw materials such as oil shale-based fine aggregate are used to prepare ultra-high performance concrete, on the one hand, the sodium hydroxide is dissolved in the mixing water to form an alkali solution to stimulate the mineral powder, fly ash and silica fume, improve their gelling activity, and react with the calcium hydroxide produced by the cement hydration to form a gelling component, increase the content of the gelling component in the concrete, and improve the strength and impermeability. On the other hand, the phosphoric acid in the phosphogypsum gradually dissolves and reacts with part of the sodium hydroxide / potassium to form phosphate and water, wherein the water can provide the required water for the above-mentioned volcanic ash reaction. The phosphate reacts with the magnesium oxide in the oil shale-based fine aggregate to form a high-strength and high-viscosity gelling component struvite, which can effectively improve the combination of the oil shale-based fine aggregate with the concrete matrix and improve the mechanical strength and impermeability of the concrete structure. In addition, the phosphogypsum also has a retarding effect, which helps to prolong the setting time of concrete and maintain better fluidity / workability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention, and do not constitute an improper limitation of the present invention.

[0024] Figure 1 1 is a compressive strength test diagram of the following Example 1.

[0025] Figure 2 It is the water-proof performance test diagram of the following Examples 1 to 8. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with specific examples, which are only used to illustrate the present invention and are not used to limit the scope of the present invention. The preferred implementation methods and materials described in the text are only for demonstration purposes. It should be noted that all professional and scientific terms used in the text have the same meanings as those familiar to those skilled in the art, unless otherwise defined.

[0027] In addition, the reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions.

[0028] Example 1

[0029] A method for preparing an oil shale-based aggregate ultra-high performance concrete material comprises the following steps:

[0030] (1) Mix oil shale slag, waste glass powder, lithium slag powder and magnesium oxide in a mass ratio of 60:35:7:18 and stir evenly to form a mixed powder, wherein: the fineness of the oil shale slag is 40 mesh, the fineness of the glass powder, lithium slag powder and magnesium oxide are all 200 mesh, and the softening temperature of the waste glass powder is about 520-550°C. Then heat the mixed powder to 590°C at a heating rate of 10°C / min and keep it warm for 30 minutes. After completion, cool it to room temperature, crush the sintered product, screen it, and grade it according to the mass ratio of particle size 0.5-1mm, 1-2mm, 2-3mm=2:1:1 to obtain oil shale-based fine aggregate for standby use.

[0031] (2) Mix phosphogypsum powder, sodium stearate powder and silane coupling agent KH550 and stir evenly, wherein the sodium stearate accounts for 30% of the mass of the phosphogypsum powder and the silane coupling agent KH550 accounts for 2.2% of the mass of the phosphogypsum powder. Then grind the obtained mixed powder to obtain modified phosphogypsum powder with a fineness of 300 meshes for standby use.

[0032] (3) Take the following raw materials: 115 parts by weight of composite cementitious material with a fineness of 400 mesh, 260 parts by weight of the oil shale-based fine aggregate, 80 parts by weight of fly ash, 150 parts by weight of silica fume, 54 parts by weight of the modified phosphogypsum powder, 23 parts by weight of polypropylene fiber (length 12 mm, diameter 0.3 mm), 2 parts by weight of polycarboxylic acid water reducer, and 1.7 parts by weight of potassium hydroxide. Wherein: the composite cementitious material is composed of 42.5 ordinary Portland cement and mineral powder, and the Portland cement accounts for 35wt.%. The above raw materials are mixed and stirred evenly, and then mixing water is added at a mass ratio of water to composite cementitious material = 0.2:1 and stirred for 3 minutes to obtain a concrete material.

[0033] The fluidity of the concrete material prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GB / T 2419-2005). The 28d compressive strength (such as Figure 1 As shown), 28d water seepage height (as shown Figure 2 The results are shown in Table 1 below.

[0034] Table 1

[0035] Test indicators Liquidity 28d compressive strength 28d water seepage height Test Results 218mm 109.6MPa 13.3mm

[0036] Example 2

[0037] A method for preparing an oil shale-based aggregate ultra-high performance concrete material comprises the following steps:

[0038] (1) Mix oil shale slag, waste glass powder, lithium slag powder and magnesium oxide in a mass ratio of 50:30:6:15 and stir evenly to form a mixed powder, wherein: the fineness of the oil shale slag is 20 mesh, the fineness of the glass powder, lithium slag powder and magnesium oxide are all 400 mesh, and the softening temperature of the waste glass powder is about 520-550°C. Then heat the mixed powder to 600°C at a heating rate of 10°C / min and keep it warm for 20 minutes. After completion, cool it to room temperature, crush the sintered product, screen it, and grade it according to the mass ratio of particle size 0.5-1mm, 1-2mm, 2-3mm=1.5:1:1 to obtain oil shale-based fine aggregate for standby use.

[0039] (2) Mix phosphogypsum powder, sodium stearate powder and silane coupling agent KH570 and stir evenly, wherein the sodium stearate accounts for 33% of the mass of the phosphogypsum powder and the silane coupling agent KH550 accounts for 2.5% of the mass of the phosphogypsum powder. Then grind the obtained mixed powder to obtain modified phosphogypsum powder with a fineness of 400 mesh, which is set aside.

[0040] (3) Take the following raw materials: 130 parts by weight of a composite cementitious material with a fineness of 350 mesh, 280 parts by weight of the oil shale-based fine aggregate, 85 parts by weight of fly ash, 170 parts by weight of silica fume, 62 parts by weight of the modified phosphogypsum powder, 25 parts by weight of basalt fiber (length 20 mm, diameter 0.3 mm), 2.8 parts by weight of polycarboxylic acid water reducer, 1 part by weight of potassium hydroxide, and 1 part by weight of sodium hydroxide. The composite cementitious material is composed of 42.5 ordinary Portland cement and mineral powder, and the Portland cement accounts for 40wt.%. The above raw materials are mixed and stirred evenly, and then mixing water is added at a mass ratio of water to composite cementitious material = 0.25:1 and stirred for 3 minutes to obtain a concrete material.

[0041] The fluidity of the concrete material prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GB / T 2419-2005). The 28d compressive strength, 28d water seepage height (such as 0.040 m / s) of the specimens prepared from the concrete material prepared in this embodiment were tested according to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2009) and the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). Figure 2 The results are shown in Table 2 below.

[0042] Table 2

[0043] Test indicators Liquidity 28d compressive strength 28d water seepage height Test Results 223mm 104.1MPa 15.7mm

[0044] Example 3

[0045] A method for preparing an oil shale-based aggregate ultra-high performance concrete material comprises the following steps:

[0046] (1) Mix oil shale slag, waste glass powder, lithium slag powder and magnesium oxide in a mass ratio of 70:42:8.5:23 and stir evenly to form a mixed powder, wherein: the fineness of the oil shale slag is 50 mesh, the fineness of the glass powder, lithium slag powder and magnesium oxide are all 300 mesh, and the softening temperature of the waste glass powder is about 520-550°C. Then heat the mixed powder to 580°C at a heating rate of 10°C / min and keep it warm for 35 minutes. After completion, cool it to room temperature, crush the sintered product, screen it, and grade it according to the mass ratio of particle size 0.5-1mm, 1-2mm, 2-3mm=1.5:1:1 to obtain oil shale-based fine aggregate for standby use.

[0047] (2) Mix phosphogypsum powder, sodium stearate powder and silane coupling agent KH560 and stir evenly, wherein the sodium stearate accounts for 25% of the mass of the phosphogypsum powder and the silane coupling agent KH550 accounts for 2% of the mass of the phosphogypsum powder. Then grind the obtained mixed powder to obtain modified phosphogypsum powder with a fineness of 400 mesh, which is set aside.

[0048] (3) Take the following raw materials: 110 parts by weight of composite cementitious material with a fineness of 300 mesh, 230 parts by weight of the oil shale-based fine aggregate, 70 parts by weight of fly ash, 140 parts by weight of silica fume, 50 parts by weight of the modified phosphogypsum powder, 20 parts by weight of steel fiber (length 30 mm, diameter 0.1 mm), 1.6 parts by weight of naphthalene-based water reducer, and 1 part by weight of potassium hydroxide. The composite cementitious material is composed of 42.5 ordinary Portland cement and mineral powder, and the Portland cement accounts for 30wt.%. The above raw materials are mixed and stirred evenly, and then mixing water is added at a mass ratio of water to composite cementitious material = 0.17:1 and stirred for 3 minutes to obtain a concrete material.

[0049] The fluidity of the concrete material prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GB / T 2419-2005). The 28d compressive strength, 28d water seepage height (such as 0.040 m / s) of the specimens prepared from the concrete material prepared in this embodiment were tested according to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2009) and the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). Figure 2 The results are shown in Table 3 below.

[0050] Table 3

[0051] Test indicators Liquidity 28d compressive strength 28d water seepage height Test Results 211mm 113.8MPa 10.2mm

[0052] Example 4

[0053] A method for preparing an oil shale-based aggregate ultra-high performance concrete material comprises the following steps:

[0054] (1) The oil shale slag is graded according to a mass ratio of 0.5-1 mm, 1-2 mm, and 2-3 mm in particle size = 2:1:1 to obtain oil shale-based fine aggregate for later use.

[0055] (2) Take the following raw materials: 115 parts by weight of composite cementitious material with a fineness of 400 mesh, 260 parts by weight of oil shale-based fine aggregate of this embodiment, 80 parts by weight of fly ash, 150 parts by weight of silica fume, 54 parts by weight of modified phosphogypsum powder of the above embodiment 1, 23 parts by weight of polypropylene fiber (length 12 mm, diameter 0.3 mm), 2 parts by weight of polycarboxylic acid water reducer, and 1.7 parts by weight of potassium hydroxide. The composite cementitious material is composed of 42.5 ordinary Portland cement and mineral powder, and the Portland cement accounts for 35wt.%. The above raw materials are mixed and stirred evenly, and then mixing water is added at a mass ratio of water to composite cementitious material = 0.2:1 and stirred for 3 minutes to obtain a concrete material.

[0056] The fluidity of the concrete material prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GB / T 2419-2005). The 28d compressive strength, 28d water seepage height (such as 0.040 m / s) of the specimens prepared from the concrete material prepared in this embodiment were tested according to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2009) and the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). Figure 2 The results are shown in Table 4 below.

[0057] Table 4

[0058] Test indicators Liquidity 28d compressive strength 28d water seepage height Test Results 156mm 82.7MPa 36.4mm

[0059] Example 5

[0060] A method for preparing an oil shale-based aggregate ultra-high performance concrete material comprises the following steps:

[0061] (1) Mix oil shale slag, waste glass powder and lithium slag powder in a mass ratio of 50:30:6 and stir evenly to form a mixed powder, wherein: the fineness of the oil shale slag is 20 mesh, the fineness of the glass powder and the lithium slag powder are both 400 mesh, and the softening temperature of the waste glass powder is about 520-550°C. Then heat the mixed powder to 600°C at a heating rate of 10°C / min and keep it warm for 20 minutes. After completion, cool it to room temperature, crush the sintered product, screen it, and grade it according to the mass ratio of particle size 0.5-1mm, 1-2mm, 2-3mm=1.5:1:1 to obtain oil shale-based fine aggregate for standby use.

[0062] (2) Take the following raw materials: 130 parts by weight of composite cementitious material with a fineness of 350 mesh, 280 parts by weight of the oil shale-based fine aggregate of this embodiment, 85 parts by weight of fly ash, 170 parts by weight of silica fume, 62 parts by weight of modified phosphogypsum powder of the above embodiment 2, 25 parts by weight of basalt fiber (length 20 mm, diameter 0.3 mm), 2.8 parts by weight of polycarboxylic acid water reducer, 1 part by weight of potassium hydroxide, and 1 part by weight of sodium hydroxide. The composite cementitious material is composed of 42.5 ordinary Portland cement and mineral powder, and the Portland cement accounts for 40wt.%. The above raw materials are mixed and stirred evenly, and then mixing water is added at a mass ratio of water to composite cementitious material = 0.25:1 and stirred for 3 minutes to obtain a concrete material.

[0063] The fluidity of the concrete material prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GB / T 2419-2005). The 28d compressive strength, 28d water seepage height (such as 0.040 m / s) of the specimens prepared from the concrete material prepared in this embodiment were tested according to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2009) and the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). Figure 2 The results are shown in Table 5 below.

[0064] Table 5

[0065] Test indicators Liquidity 28d compressive strength 28d water seepage height Test Results 229mm 91.2MPa 23.5mm

[0066] Example 6

[0067] A method for preparing an oil shale-based aggregate ultra-high performance concrete material comprises the following steps:

[0068] (1) Mix oil shale slag, lithium slag powder and magnesium oxide in a mass ratio of 60:7:18 and stir evenly to form a mixed powder, wherein the fineness of the oil shale slag is 40 mesh, and the fineness of the lithium slag powder and magnesium oxide are both 200 mesh. Then heat the mixed powder to 590°C at a heating rate of 10°C / min and keep it warm for 30 minutes. After completion, cool it to room temperature to obtain oil shale-based fine aggregate, which is set aside.

[0069] (2) Take the following raw materials: 115 parts by weight of composite cementitious material with a fineness of 400 mesh, 260 parts by weight of oil shale-based fine aggregate of this embodiment, 80 parts by weight of fly ash, 150 parts by weight of silica fume, 54 parts by weight of modified phosphogypsum powder of the above embodiment 1, 23 parts by weight of polypropylene fiber (length 12 mm, diameter 0.3 mm), 2 parts by weight of polycarboxylic acid water reducer, and 1.7 parts by weight of potassium hydroxide. The composite cementitious material is composed of 42.5 ordinary Portland cement and mineral powder, and the Portland cement accounts for 35wt.%. The above raw materials are mixed and stirred evenly, and then mixing water is added at a mass ratio of water to composite cementitious material = 0.2:1 and stirred for 3 minutes to obtain a concrete material.

[0070] The fluidity of the concrete material prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GB / T 2419-2005). The 28d compressive strength, 28d water seepage height (such as 0.040 m / s) of the specimens prepared from the concrete material prepared in this embodiment were tested according to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2009) and the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). Figure 2 The results are shown in Table 6 below.

[0071] Table 6

[0072]

[0073]

[0074] Example 7

[0075] A method for preparing an oil shale-based aggregate ultra-high performance concrete material comprises the following steps:

[0076] Take the following raw materials: 110 parts by weight of composite cementitious material with a fineness of 300 mesh, 230 parts by weight of oil shale-based fine aggregate of the above-mentioned Example 3, 70 parts by weight of fly ash, 140 parts by weight of silica fume, 50 parts by weight of phosphogypsum powder with a fineness of 400 mesh, 20 parts by weight of steel fiber (length 30 mm, diameter 0.1 mm), 1.6 parts by weight of naphthalene-based water reducer, and 1 part by weight of potassium hydroxide. Among them, the composite cementitious material is composed of 42.5 ordinary Portland cement and mineral powder, and the Portland cement accounts for 30wt.%. The above raw materials are mixed and stirred evenly, and then mixing water is added at a mass ratio of water to composite cementitious material = 0.17:1 and stirred for 3 minutes to obtain a concrete material.

[0077] The fluidity of the concrete material prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GB / T 2419-2005). The 28d compressive strength, 28d water seepage height (such as 0.040 m / s) of the specimens prepared from the concrete material prepared in this embodiment were tested according to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2009) and the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). Figure 2 The results are shown in Table 7 below.

[0078] Table 7

[0079] Test indicators Liquidity 28d compressive strength 28d water seepage height Test Results 177mm 110.4MPa 12.8mm

[0080] Example 8

[0081] A method for preparing an oil shale-based aggregate ultra-high performance concrete material comprises the following steps:

[0082] Take the following raw materials: 130 parts by weight of composite cementitious material with a fineness of 350 mesh, 280 parts by weight of oil shale-based fine aggregate of the above embodiment 2, 85 parts by weight of fly ash, 170 parts by weight of silica fume, 62 parts by weight of modified phosphogypsum powder of the above embodiment 2, 25 parts by weight of basalt fiber (length 20 mm, diameter 0.3 mm), and 2.8 parts by weight of polycarboxylate water reducer. Among them, the composite cementitious material is composed of 42.5 ordinary Portland cement and mineral powder, and the Portland cement accounts for 40wt.%. The above raw materials are mixed and stirred evenly, and then mixing water is added at a mass ratio of water to composite cementitious material = 0.25:1 and stirred for 3 minutes to obtain concrete material.

[0083] The fluidity of the concrete material prepared in this embodiment was tested according to the "Method for Determining the Fluidity of Cement Mortar" (GB / T 2419-2005). The 28d compressive strength, 28d water seepage height (such as 0.040 m / s) of the specimens prepared from the concrete material prepared in this embodiment were tested according to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082-2009) and the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019). Figure 2 The results are shown in Table 8 below.

[0084] Table 8

[0085] Test indicators Liquidity 28d compressive strength 28d water seepage height Test Results 226mm 93.5MPa 25.2mm

[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an oil shale-based aggregate ultra-high performance concrete material, characterized in that: The steps include: (1) mixing oil shale slag, glass powder, lithium slag powder and magnesium oxide uniformly and then sintering them, cooling them to room temperature, and crushing the sintered products to obtain oil shale-based fine aggregate; (2) mixing phosphogypsum powder, sodium stearate powder and liquid silane coupling agent and stirring them uniformly, and then grinding the obtained mixed powder to obtain modified phosphogypsum powder; (3) The following raw materials are taken: 110-130 parts by weight of a composite cementitious material, 230-280 parts by weight of the oil shale-based fine aggregate, 70-85 parts by weight of fly ash, 140-170 parts by weight of silica fume, 50-62 parts by weight of the modified phosphogypsum powder, 20-25 parts by weight of fiber, 1.6-2.8 parts by weight of a water reducer, and 1-2 parts by weight of sodium hydroxide and / or potassium hydroxide; the composite cementitious material is composed of silicate cement and mineral powder, wherein the silicate cement accounts for 30-40 wt.%; the above raw materials are mixed and then mixed with mixing water at a water-cement ratio of 0.17-0.25, and stirred evenly to obtain a concrete material.

2. The method for preparing the oil shale-based aggregate ultra-high performance concrete material according to claim 1, characterized in that: In step (1), the ratio of the oil shale slag, glass powder, lithium slag powder and magnesium oxide is 50-70 parts by weight: 30-42 parts by weight: 6-8.5 parts by weight: 15-23 parts by weight; Optionally, in step (1), the fineness of the oil shale slag is 20-50 mesh; Optionally, in step (1), the fineness of the glass powder, lithium slag powder and magnesium oxide is not less than 200 mesh.

3. The method for preparing the oil shale-based aggregate ultra-high performance concrete material according to claim 1, characterized in that: In step (1), the sintering temperature is higher than the softening temperature of the glass powder, and the sintering time is 20 to 35 minutes.

4. The method for preparing the oil shale-based aggregate ultra-high performance concrete material according to claim 3, characterized in that: In step (1), the softening temperature of the glass powder does not exceed 600° C. to reduce the energy consumption of sintering; preferably, in step (1), the glass powder is made of waste glass.

5. The method for preparing the oil shale-based aggregate ultra-high performance concrete material according to claim 1, characterized in that: In step (1), the particle size of the oil shale-based fine aggregate is 0.5 to 3 mm; Preferably, the mass ratio of particles with particle sizes of 0.5-1 mm, 1-2 mm, and 2-3 mm in the oil shale-based fine aggregate is 1.5-2:1:

1.

6. The method for preparing the oil shale-based aggregate ultra-high performance concrete material according to claim 1, characterized in that: In step (2), the sodium stearate is 25-33% of the mass of the phosphogypsum powder, and the liquid silane coupling agent is 2-2.5% of the mass of the phosphogypsum powder.

7. The method for preparing the oil shale-based aggregate ultra-high performance concrete material according to claim 1, characterized in that: In step (2), the liquid silane coupling agent includes at least one of KH550, KH560, and KH570.

8. The method for preparing the oil shale-based aggregate ultra-high performance concrete material according to any one of claims 1 to 7, characterized in that: The fineness of the composite cementitious material and gypsum powder is 300-400 meshes.

9. The method for preparing the oil shale-based aggregate ultra-high performance concrete material according to any one of claims 1 to 7, characterized in that: In step (3), the fiber includes at least one of steel fiber, organic fiber, and basalt fiber; Optionally, the organic fiber includes at least one of polyethylene fiber, polyvinyl alcohol fiber, polypropylene fiber, and polyacrylonitrile fiber; Optionally, in step (3), the fiber has a length of 12 to 30 mm and a diameter of 0.1 to 0.3 mm.

10. The method for preparing the oil shale-based aggregate ultra-high performance concrete material according to any one of claims 1 to 7, characterized in that: In step (3), the water reducer includes at least one of a polycarboxylate water reducer, a naphthalene-based water reducer, a melamine-based water reducer, a lignin sulfonate water reducer, and a melamine water reducer.

Citation Information

Patent Citations

  • Method for producing foam microcrystal glass by utilizing composite industrial residue and product

    CN102838283A

  • Superfine common glass powder doped active powder concrete and preparation method thereof

    CN103172323A

  • Method for preparing ceramsite for concrete material from oil shale residues

    CN113149690A

  • Ultra-high performance concrete and preparation method thereof

    CN116924741A

  • Haydite prepared from dregs of oil shale, and preparation method

    CN1872782A

Cited By

  • Preparation method of modified oyster shell and steel fiber based 3D printing ecological concrete

    CN120554082A

  • Preparation method of modified oyster shell and steel fiber-based 3D printing ecological concrete

    CN120554082B